Antibacterial activity of cocoa pod husk phenolic extract against Escherichia coli for food processing. Issue 1 (April 2020) - Diniardi, E M; Argo, B D; Wibisono, Y
Abstract: Cocoa pod husk (CPH) which is a waste of cocoa plantation contains phenolic compounds which can be used as antibacterial agents. Phenolic compounds in CPH include phenolic acids, flavonoids and flavones. The aim of this study was to analyze the antibacterial activity of CPH extract whis was extracted by using Microwave-Assisted Extraction (MAE) method. Extraction using 96% ethanol solvent with a ratio of 1:4, 1:6 and 1:8 (w/v) for 2, 3 and 4 minutes, respectively. The extraction results with the highest total phenolic content were tested their antibacterial activity using a disk diffusion method at an extract concentration of 5, 7.5, 10 mg/mL and 15 mg/mL with three replications, respectively. The highest total phenolic content of 453 mg GAE/g dry extract was obtained from MAE treatment with a solvent ratio of 1:4 (w/v) for 4 minutes. The results of the antibacterial activity of extracts against Escherichia coli showed that inhibitory zones had formed at a concentration of 5 mg/mL. The width of the inhibition zone increases as the concentration of extract increases.